Roman woodworking - Ulrich, Roger Bradley (Yale University Press, 2007)
"This book presents an authoritative and detailed survey of the art of woodworking in the ancient Roman world. Illustrated with over 200 line drawings and photographs, 'Roman Woodworking' covers topics such as the training and guild memberships of Roman carpenters, woodworking tools and techniques, the role of timber in construction and the availability of trees, and interior woodwork and furniture making. It also includes an extensive glossary of fully defined terms. This comprehensive book displays the accomplishment of the Roman woodworkers and their high skill and knowledge of materials and tools. Ulrich helps bring to light the importance of wooden projects and structures in Roman daily life and provides a wealth of information not only for classicists but also for those interested in the history of technology and the history of woodworking"--Publisher's description